The Selby-Russell Dispute Regarding the Nonreporting of Critical Data in the Mega-Mouse Experiments of Drs William and Liane Russell That Spanned Many Decades: What Happened, Current Status, and Some Ramifications - P. B. Selby (SAGE Publishing, 2020)
The Russells began their studies of the hereditary effects of radiation in the late 1940s, and their experiments contributed much to what is known about the induction of gene mutations in mice. I had a close association with them for about 26 years, and they relied on me considerably for database management and statistical support. In 1994, I was shocked to discover that, in experiments on males, they had failed to report numerous spontaneous mutations that arose during the perigametic interval and were detected as clusters of mutations. I realized that their nondisclosure of this information meant that the decades-long application of their data to estimate hereditary risks of radiation to humans using the doubling-dose approach had resulted in a several-fold overestimation of risk. I accordingly reported the situation to funding agencies. The resulting complicated situation is referred to here as the Selby-Russell Dispute. Highlights of the resulting investigation, as well as what occurred afterward, are described, and reasons will be provided to show why, in my opinion, the hereditary risk from radiation in humans was likely overestimated by at least 10-fold because the Russells decided not to report critical information from their massive experiments.